The wisdom of psychopaths : Lessons in life from saints, spies and serial killers - Dutton, Kevin, 1967- (Arrow, 2013)
In this adventure into the world of psychopaths, Kevin Dutton reveals that there is a 'scale of madness' along which we all sit. He shows that there is a fine line separating a brilliant surgeon and a serial killer, illustrating the spectrum of psychopathy with some insightful and startling case studies.